Muscle strengthening activities and mortality with considerations by hearing sensitivity. (3rd May 2016) - Loprinzi, Paul D.
Abstract: Objective : Research demonstrates that hearing impairment is associated with premature all-cause mortality. Emerging work indicates that physical activity is associated with hearing sensitivity and muscle strengthening activities (MSA) are favorably associated mortality in the general population. Whether MSA can promote survival among those with hearing impairment is, at this point, unknown, which was this study's objective. Design : Prospective cohort study using data from the 2003–2006 National Health and Nutrition Examination Survey, with follow-up through 2011. Study sample : 1482 adult (20–85 years) participants comprised the analytic sample. Results : Among the study participants, 152 died over the follow-up period (10.26%; unweighted); the unweighted median follow-up period was 89 months (IQR = 74–98 months). Among adults with moderate or greater hearing loss who achieved the United States Department of Health and Human Services guidelines for MSA (2 + sessions/week), they were at a 71% reduced risk of all-cause mortality (HRadjusted  =  0.29; 95% CI: 0.10–0.83; P  =   0.02). Conclusions : MSA may help to prolong survival among those with worse hearing impairment.